Environmental aminomethylphosphonic acid (AMPA) exposure increased the risk of spontaneous abortion through lactate-induced JunB lactylation in trophoblast - Chengcai Kong; Rong Li; Xiaoying Wang; Lijuan Li; Nannan Kang; Xin Zhen; Yishan Dong; Guijun Yan (Ecotoxicology and Environmental Safety, 2025)
The etiology of spontaneous abortion (SA) is complex, and the underlying mechanisms remain largely elusive. Environmental toxins have been implicated in the increased occurrence of SA. However, the association between aminomethylphosphonic acid (AMPA) exposure and SA has not yet been established. We found that AMPA, along with the lactate were significantly elevated in villous tissues from SA patients compared to normal controls, with a robust positive correlation between AMPA and lactate concentrations. More importantly, AMPA exposure induced SA in C57BL/6 mice probably through the dysfunctions of human trophoblast cell. Further studies indicated that the L-lactate production which can be induced by AMPA via PPARγ/ANGPTL4 pathway caused similar defects of human trophoblast cells. A global elevation of protein lactylation has been detected in the villous tissues from SA patients as well as AMPA or lactate treated human trophoblast cells. Pan-Kla antibody coimmunoprecipitation coupled with mass spectrometry of AMPA or lactate treated human trophoblast cells revealed JunB, which was reduced in the placenta villus from SA patients and AMPA/lactate treated human trophoblast cells, could be lactylated at lysine (K) 36. JunB K36R mutation abolished JunB lactylation and ameliorated AMPA induced JunB loss via ubiquitination in human trophoblast cells. In comparison to wild type JunB, JunB K36R mutation had better protective roles in AMPA induced trophoblast dysfunctions. In conclusion, our results demonstrate that AMPA exposure promotes lactate production via the PPARγ/ANGPTL4 pathway, which subsequently inhibits the proliferation, migration and invasion of trophoblasts through JunB K38 lactylation, ultimately leading to SA.